STRUCTURAL BEHAVIOR AND PERFORMANCE OF HOT-ROLLED WIDE FLANGE CASTELLATED STEEL BEAMS: INSIGHTS FROM FINITE ELEMENT ANALYSIS - Cipto Wahyu; budiman budiman; Basit Al Hanif (University Muhammadiyah Jakarta, 2025)
Castellated steel beams, produced by cutting solid cross-sections, enhance the moment of inertia without increasing self-weight but remain vulnerable to lateral–torsional buckling (LTB) and Vierendeel action. This study investigates the nonlinear behavior of IWF 200×100×5.5×9 beams with spans of 8–10 meters using ABAQUS and the modified Riks algorithm. Results reveal that LTB is the governing failure mode, consistent with AISC 360 predictions. Circular web openings provide 2–7% higher ultimate capacity at short spans, though their performance aligns with hexagonal openings for longer spans. Hexagonal openings, however, reduce deflections by 15–20%, indicating improved serviceability. Strengthening strategies are proposed, including stiffeners, lateral bracing, partial closure of web openings near supports, and optimization of opening ratios between 50–70%, achieving an effective balance between strength and deflection control. The findings highlight the critical influence of opening geometry and span on structural performance and provide actionable guidance for the design and optimization of castellated steel beams. This work advances understanding of perforated steel behavior under bending and offers practical solutions for enhancing both ultimate capacity and serviceability in engineering applications.Keywords: Castellated steel beams, nonlinear analysis, lateral–torsional buckling, ABAQUS, structural optimization